KELAM DİLİNİN KURGUSAL NİTELİĞİ-Din-Kelam İlişkisi ve Kelamda Kavramsal Soyutlamanın Zorunluluğu- - Galip Türcan (İslami İlimler Dergisi)
A comparision between the religion and kalam from the viewpoint of nature and aim procures to form an opinion about the apperance of kalam and its function which it realized throughout its own history. Kalam placed the religious concepts into its own terminology, but abstracted these concepts by the reason of theological worries and earned them new contents that would support its own aim and function. Going away from the searching of factual reality and aiming to solve the theological problem in favour of religious comments on which the political preferences were effective, the kalam improved a fictitious language in the view of terminology.